2021
DOI: 10.1039/d1cp03255k
|View full text |Cite
|
Sign up to set email alerts
|

Computational UV spectra for amorphous solids of small molecules

Abstract: Ices in the interstellar medium largely exist as amorphous solids composed of small molecules including ammonia, water, and carbon dioxide. Describing gas-phase molecules can be readily accomplished with current high-level...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…From previous benchmarking on clusters with 8 molecules and CAM-B3LYP/6-311G(d,p), the amorphous spectra predictions for water, ammonia, and carbon dioxide are off from experiment by 0.51, 0.32, and 0.24 eV, respectively. 31 Though such a shift could put the amorphous style clusters more in line with the experiments, such would still likely fall short. However, the amorphous clusters do provide a possible clue as to the origins of lower energy feature in their nonzero oscillator strength n → σ* transitions.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…From previous benchmarking on clusters with 8 molecules and CAM-B3LYP/6-311G(d,p), the amorphous spectra predictions for water, ammonia, and carbon dioxide are off from experiment by 0.51, 0.32, and 0.24 eV, respectively. 31 Though such a shift could put the amorphous style clusters more in line with the experiments, such would still likely fall short. However, the amorphous clusters do provide a possible clue as to the origins of lower energy feature in their nonzero oscillator strength n → σ* transitions.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Amorphous carbonic acid is simulated by generating 40 randomized clusters. 31 Each cluster consists of 8 carbonic acid molecules composed of the two lowest energy conformational isomers of the monomer. Previous work has shown that 8 carbonic acid molecules are enough to achieve convergence in the spectra, 20 and the same number produces similar behavior in related carbon dioxide clusters.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 3 more Smart Citations